Design of Church Financial Statements Based on Interpretation of Financial Accounting Standards (Isak) 35 - Mei Hotma Mariati Munte; Jadongan Sijabat; Solomon Slow Panggabean (Jurnal Indonesia Sosial Teknologi, 2024)
The church is an entity that aims not to make a profit, so financial accountability is an important aspect of the church. Good financial accountability can only be realized if the financial reports’ church accepts financial accounting standards. The financial accounting standard governing the financial reporting financial reporting of nonprofit-reinterpretation of Financial Accounting Standards (ISAK) 35. By applying ISAK 35 in presenting church financial reports, it is hoped that parties interested in the church can assess the performance of church management and increase the congregation’s trust in the church administrator. The research location is at the HKBP Bandar Klippa Resort Epiphanias Tembung District X Medan Aceh. Data was collected through interviews and documentation. The validity of the data was tested by the triangulation method. This study aims to present church financial reports based on ISAK 35. In 2022, HKBP Bandar Klippa will have a Rp deficit (39.736.895). Also, in 2022, there were some additional fixed assets. There are two units of fans, 1 unit of keyboard, and 1 unit of audio mics, and the Sunday school building will be inaugurated in November 2023. The change in net assets was influenced by a deficit in 2022, which becomes Rp 1.021.626.010. HKBP Bandar Klippah's cash flow activities consist of operations and investments.